1950
DOI: 10.1002/jsfa.2740010504
|View full text |Cite
|
Sign up to set email alerts
|

An examination of polymerized pyrethrins

Abstract: The resinous material formed by polymerization of a highly purified pyrethrum concentrate has been examined. It was insoluble in cold light petroleum or deodorized kerosene, and gave high values for apparent pyrethrins by the Seil or mercuryreduction methods, although it was devoid of insecticidal effect on houseflies. In these respects it resembled the additional ' pyrethrins ' recently shown' to be extracted by chloroform or by warm light petroleum from pyrethrum flowefs, differing only in its higher content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1951
1951
1969
1969

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…for 3 months, produced resinous material Division of Entomology, University of California, Berkeley, Calif. 94720 1 Present address, Department of Agricultural Chemistry, National Taiwan University, Taipei, Taiwan which, after hydrolysis, yielded crystalline chrysanthemumic and chrysanthemumdicarboxylic acids; this finding supports the view that the photodecomposition involves only the cyclopentenolone portion of the esters, the acids not being attacked (Campbell and Mitchell, 1950). When films of pyrethrum oleoresin extract were irradiated with a tungsten light, Brown and Phipers (1955) found that the green-colored material in the extracts catalyzed degradation of the chrysanthemumic acid moiety but not the slower changes taking place in the cyclopentenolone moiety.…”
mentioning
confidence: 55%
“…for 3 months, produced resinous material Division of Entomology, University of California, Berkeley, Calif. 94720 1 Present address, Department of Agricultural Chemistry, National Taiwan University, Taipei, Taiwan which, after hydrolysis, yielded crystalline chrysanthemumic and chrysanthemumdicarboxylic acids; this finding supports the view that the photodecomposition involves only the cyclopentenolone portion of the esters, the acids not being attacked (Campbell and Mitchell, 1950). When films of pyrethrum oleoresin extract were irradiated with a tungsten light, Brown and Phipers (1955) found that the green-colored material in the extracts catalyzed degradation of the chrysanthemumic acid moiety but not the slower changes taking place in the cyclopentenolone moiety.…”
mentioning
confidence: 55%
“…Trans., 60, 1235-40 (1941. (2) Daigle, E. C., and Lee, J. H., Petroleum Refiner, 27, No. 9, 492-5 (1948).…”
Section: Obtaining Inverse Matrixmentioning
confidence: 99%